Digital user behaviour of academicians in a conflict zone, Kashmir: Comparing log analysis of electronic resources in the times of conflict and peace. Issue 2 (1st April 2014) - Gul, Sumeer; Ahmad Shah, Tariq; Ahmad, Suhail
Abstract : Purpose: – The aim of this paper is to explore digital user behaviour of academicians in Kashmir (Indian Administered) in the times of conflict (2008-2010) and peace (2011-2012). It is an attempt to investigate the influence of political conditions on the usage of electronic resources. Design/methodology/approach: – Transaction logs in the form of COUNTER reports from Project MUSE database that represent usage at University of Kashmir, were mined for five years – January 2008 to December 2012. The data was divided in to two time periods; conflict period – 2008 to 2010 and peace period – 2011 to 2012. Findings: – There is a strong relationship between peace, conflict and e-resource usage. The results confirm peace and conflict as explanatory factors on the use of electronic resources in conflict zones, like Kashmir. Research limitations/implications: – Understanding how users behave in the online academic environments, the academic administrators can help to satisfy the perceptions and needs of users associated with the electronic resource settings. Practical implications: – The study shows that more attention should be given to prevail peace in conflict zones in order to maximise the use of e-resources. Originality/value: – The study is the first of its kind as it is trying to relate the user behaviour with political setups in a conflict zone, Kashmir.